Comparison of Methods for Calculating Fragmentation of Blast Muck Piles in Quarries - Nowak-Szpak, Anna; Wesoły, Michał; Bajcar, Adam (Wydział Geoinżynierii, Górnictwa i Geologii Politechniki Wrocławskiej, 2024)
The size distribution and fragmentation level of the blasted rock mass are crucial factors in enhancing the efficiency of loading, transportation, crushing, and milling processes. This article pro-vides a comparative analysis of grain size distribution curves derived from image analysis using vari-ous methods. The first method compares representative fragments of the muck pile through manual analysis, commercial software, and an Open-Source Algorithm. The second method evaluates the grain size distribution curves of the entire muck pile, utilizing both commercial software and an open-source algorithm.
Mining Science, Vol. 31, 2024, s. 145-162
Keywords: górnictwo; geologia; geoinżynieria; fragmentation; fragment size distribution; fracture; blasting; quarries